Analysis of The Instillation of Malay Cultural Values in Science Learning for Grade IV at SDN 064965 Sidodame, Medan City - Ritonga, Yuspita (Berpusi Publishing, 2024)
This study aims to analyze the instillation of Malay cultural values in science learning in grade IV of SDN 064965 Sidodame , Medan City. The background of this study is based on the importance of preserving local culture amidst the rapid flow of globalization, as well as the still low integration of Malay culture in the learning process in elementary schools. The method used in this study is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The research subjects included grade IV teachers, students, and school officials. The results of the study indicate that Malay cultural values such as religiosity, politeness, mutual cooperation, and local wisdom have been instilled in science learning, but their implementation has not been optimal due to limited learning media, teacher understanding, and lack of institutional support. These obstacles are attempted to be overcome through the search for additional references, curriculum adaptation, and teachers' personal initiatives. This study concludes that the instillation of Malay cultural values in science learning has great potential in shaping the character of students who are cultured and moral, but requires further strategies, resources, and support from various parties.